(untitled) (Research, Society and Development, 2023)
This research aimed to analyze and evalute possible anthopic impacts on the vegetal cover and conservation efficiency inside of the Morro de Santo Antônio Natural Monument (MONAT), located in the State of Mato Grosso, by remote sensing. The methodology consisted of calculating the Normalized Difference Vegetation Index (NDVI) from satellite images Landsat 5 TM and Landsat 8 OLI processed in the Geographic information system QGIS. The obtained results with NDVI analyses suggest the increase of Cerrado and dense forest/Cerradão also increased both in the UC and the Buffer Zone. There was a small reduction in the cover class of exposed soil at the top of the hill, in the Conservation Unit. With the results obtained, it is possible to see that so far the unit has performed its role and has been effective in conserving the given area. Therefore, the results of this research will contribute in indentifying áreas of environmental fragility related to vegetation, as well as facilitate the application of managing techniques adequate to the environmental conservation of the Monumento Natural Estadual Morro de Santo Antônio - MT.